Hardware‐in‐the‐loop demonstration of automated demand response for distribution networks using PMU and MQTT. Issue 1 (25th January 2021) - Jahić, Admir; Hastings, John; Morrow, D John; Laverty, David
Abstract: A detailed description of an Automated Demand Response system is presented that can provide active distribution‐level voltage control, and sub‐second system‐wide frequency response services. The system is validated using a hardware‐in‐the‐loop demonstrator including synchronous machines, real and simulated Internet Protocol communications, cloud‐based computing, inexpensive measurement hardware, and state‐of‐the‐art secure IoT protocols. It is shown that a real‐time, model‐informed, demand‐response system utilising wide‐area Phasor measurement unit (PMU) data is cost effective and feasible.